Truth, Faith, Marriage, and nobility in a new version of Geoffrey Chaucerïs the Franklin tale - Chuñir A., Juana; Clavijo C., Diana
Readers of Chaucer will appreciate the vital importance of considering The Canterbury Tales as a connected Human Comedy, seeing all the tales most importantly as an expression of the Pilgrims´ characters and their relations to one another in the great drama. The Franklin´s Tale has been taken by many critics to be the final and most admirable contribution to the "Marriage Group" of tales - this tale and the preceding tales of the Wife of Bath, the Clerk, and the Merchant. The Wife´s tale insists on female dominance, the Clerk´s shows what can happen if male dominance becomes tyrannical, and the Merchant´s is a tale of a marriage born out of the stupidity and self-indulgence of one partner, and continued in the adultery and deceit of the other. The Franklin advocates tolerance and forbearance on both sides of a marriage, a willingness to do each other´s will, and to give up the hopeless notion that one can always make one´s will prevail. Marriage provides a pretext to maintain a courtly position because love furnishes the opportunity to demonstrate virtue. Chaucer paints a sad but realistic picture of the potential for love and amorous relationships in a world in which a distinction needs to be made between public and private roles. And in the end "nobility" becomes the catalyst that brings about a harmonious and edifying conclusion